Hardiness factors and university outcomes: A gender-based comparative study - Roy, Sanjoy Kumar Roy; Sarkar, Udayshankar (Goodwood Publishing, 2025)
Purpose: This study investigates the effects of the hardiness (HD) factors- commitment (CM), control (CO), and challenge (CH) on key university-based outcome variables: learning performance (LP), quality of university life (QUL), and quality of life (QOL) among business undergraduates in Bangladesh. Additionally, this study aims to assess how these associations differ by gender. Methodology/approach: Data were collected from 384 undergraduate students across 32 private universities employing a structured questionnaire. This study employed partial least squares structural equation modeling (PLS-SEM) to examine the relationships among components and necessary condition analysis (NCA) to identify the minimum levels of HD factors necessary for achieving target outcomes. Multi-group analysis (PLS-MGA) was conducted to estimate the effects of gender moderation. Results/findings: All three HD features significantly impacted LP, QUL, and QOL. Gender moderated specific relations, like CM to QOL, CO to QUL, and CH to QUL, while others showed no significant difference. NCA analysis determined that different HD variables are necessary to achieve the desired academic and life outcomes at varying levels. Conclusion: Hardiness significantly influences students’ learning performance, quality of university life, and overall life satisfaction. Integrating hardiness-enhancing strategies in university curricula can foster resilience and improve academic and life outcomes among undergraduates. Limitations: The investigation focused solely on private university undergraduate students in Dhaka city. It did not consider other personality trait variables or use advanced predictive techniques, like machine learning. Contribution: : This research extends the theoretical framework of hardiness by identifying its components’ net and necessary effects and highlighting gender-based differences.